Role of therapeutic plasmapheresis in acute liver failure in paediatric patients: a case series - Ayaz Ur Rehman; Khan, Wajiha; Khan, Salman; Awais Abbas; Qalab Abbas; Naveed Ur Rehman Siddiqui (Journal of the Pakistan Medical Association, 2024)
Paediatric acute liver failure (PALF) is a rare yet severe condition that is associated with high mortality. Apart from liver transplant, no specific therapy exists, particularly in developing countries. Evidence suggests that removal of damage-associated molecular patterns, cytokines, toxins, and other metabolites that accumulate due to impaired liver function can enhance natural recovery. Plasmapheresis can be used to remove these products; however, there is limited evidence to support this approach. This case series discusses three critically ill patients with acute liver failure who underwent plasmapheresis. The patients included a seven-year-old boy (Case 1), a 17-year-old boy (Case 2), and a 16-month-old boy (Case 3). Two patients showed significant improvement in bilirubin level, coagulation profile, inotropes requirement, and Glasgow coma scale score. Unfortunately, one patient with PALF, complicated with multi-organ dysfunction, died due to refractory shock on the fourth day of hospitalisation. —Continue